Radiation exposure during modern therapeutic endoscopic ultrasound procedures and standard alternatives - Vanella, Giuseppe; Dell’Anna, Giuseppe; Loria, Alessandro; Petrone, Maria Chiara; Del Vecchio, Antonella; Arcidiacono, Paolo Giorgio (Endoscopy International Open, 2022)
Background and study aims Therapeutic EUS (t-EUS) is increasingly being adopted in clinical practice in tertiary referral centers; however, little is known about radiation exposure (RE) metrics and diagnostic reference limits for it.Methods Kerma-area product (KAP [Gy·cm2]), Air Kerma and fluoroscopy time were retrospectively evaluated for all consecutive t-EUS procedures performed in San Raffaele Institute between 2019 and 2021. For EUS-guided choledochoduodenostomies (EUS-CDS) and gastroenterostomies (EUS-GE), an equal number of endoscopic retrograde cholangiopancreatographies (ERCPs) plus metal stenting and duodenal stents were included respectively for comparison. Results Data from 141 t-EUS procedures were retrieved (49 % pancreatic cancer, 38 % peripancreatic fluid collections). EUS-CDS (N = 44) were mainly performed fluoroless, while ERCPs required a significantly higher RE (KAP = 25 [17–55], P < 0.0001). Fluid collection drainage (EUS-FCD) with lumen apposing metal stents (LAMS, N = 26) were performed fluoroless, while EUS-FCD with double-pigtail plastic stents (DPPS, N = 28) required higher RE (KAP = 23 [13–45]). EUS-guided gallbladder drainage (EUS-GBD, N = 6) required scarce RE (KAP = 9 [3–21]) for coaxial DPPS placement. EUS-GE (N = 27) required higher RE than duodenal stenting (KAP = 44 [28–88] versus 29 [19–46], P = 0.03). EUS-guided hepaticogastrostomies (EUS-HGS, N = 10) had the highest RE among t-EUS procedures (KAP = 81 [49–123]). Procedure complexity or intervening complications were evaluated and resulted in higher RE within each procedure.Conclusions t-EUS procedures have different RE (P < 0.000001). EUS-CDS, EUS-GBD, and EUS-FCD with LAMS can be performed with no-to-mild radioscopy, unlike standard alternatives. However, radioscopy remains essential in case of technical difficulties or complications. EUS-GE and EUS-HGS involve a high RE. Endoscopists involved in t-EUS might experience RE higher than category standards, which indicates a need for increased awareness and personalized preventive measures.